Bottom-up construction of in vitro switchable memories - Padirac, Adrien (National Academy of Sciences, 2012)
Reaction networks displaying bistability provide a chemical mechanism for long-term memory storage in cells, as exemplified by many epigenetic switches. These biological systems are not only bistable but switchable, in the sense that they can be flipped from one state to the other by application of specific molecular stimuli. We have reproduced such functions through the rational assembly of dynamic reaction networks based on basic DNA biochemistry. Rather than rewiring genetic systems as synthetic biology does in vivo, our strategy consists of building simplified dynamic analogs in vitro, in an artificial, well-controlled milieu. We report successively a bistable system, a two-input switchable memory element, and a single-input push-push memory circuit. These results suggest that it is possible to build complex time-responsive molecular circuits by following a modular approach to the design of dynamic in vitro behaviors. Our approach thus provides an unmatched opportunity to study topology/function relationships within dynamic reaction networks.